Resolution 57-11: Urging the California State Legislature to Pass the California Dream Act - (:unkn) unknown (My University, 2011)
In this Resolution, recorded as File Number 110099, the Board of Supervisors of the City and County of San Francisco urges the California State Legislature to pass AB 130 and AB 131 (collectively, the California Dream Act) to provide equal access to financial aid programs for California students attending the state's public colleges and universities, regardless of a student's immigration status.
Keywords: Sanctuary Policies; California State Legislature; AB 130 and AB 131 (collectively, the California Dream Act); Financial aid programs; Students; Public colleges and universities; Immigration status; Undocumented immigrant students; City College of San Francisco and San Francisco State University; In-state tuition; AB 540; California Supreme Court; Martinez v. Regents of University of California; New Mexico and Texas; Board of Governors Fee Waiver (BOGW) Program; Cal Grants; Governor; Clerk of the Board; Lieutenant Governor; Speaker of the California State Assembly; Democratic Caucus Chair; Minority Floor Leader; San Francisco state legislative delegation